2020
DOI: 10.1016/j.omto.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits the Tumorigenesis of Follicular Thyroid Cancer via ST6GAL2-Regulated Activation of the Hippo Signaling Pathway

Abstract: Follicular thyroid carcinoma (FTC) is a common endocrine malignancy with highly aggressive features. In this study, next-generation sequencing technology was used to identify aberrant expression of sialyltransferase (ST) family members in FTC. Aberrant high expression of alpha-2,6-sialyltransferase 2 (ST6GAL2) was demonstrated to promote tumorigenesis of FTC in vitro and in vivo. Furthermore, ST6GAL2 promoted tumorigenesis by inactivating the Hippo signaling pathway. Resveratrol is a native compound extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The downregulation of ST6GAL1 decreased metalloproteinases (MMPs) expression and suppressed invasive potential of A549 and H1299 cells in vitro [ 79 ], whereas bladder cancer has ST6GAL1 upregulation, a tumor-suppressive role [ 81 ]. The upregulation of ST6GAL2 was found in different types of cancer and was associated with breast cancer with higher expression of intracellular adhesion molecule (ICAM)-1, vascular adhesion molecule (VCAM)-1, CD24, MMP2, MMP9 and C-X-C motif chemokine receptor (CXCR)4 [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of ST6GAL1 decreased metalloproteinases (MMPs) expression and suppressed invasive potential of A549 and H1299 cells in vitro [ 79 ], whereas bladder cancer has ST6GAL1 upregulation, a tumor-suppressive role [ 81 ]. The upregulation of ST6GAL2 was found in different types of cancer and was associated with breast cancer with higher expression of intracellular adhesion molecule (ICAM)-1, vascular adhesion molecule (VCAM)-1, CD24, MMP2, MMP9 and C-X-C motif chemokine receptor (CXCR)4 [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…ST6GAL2 is predominantly expressed in the adult brain and fetal tissues, and to a lesser extent in the thyroid gland, small intestine, colon, and testis (147,148). While relatively few studies have investigated the expression and role of ST6GAL2 in tumors, overexpression of this enzyme was found in select types of cancer, including breast cancer (149) and follicular thyroid carcinoma (FTC) (150). In breast cancer ST6GAL2 expression associated with poor prognosis for patients (149).…”
Section: St6gal2mentioning
confidence: 99%
“…Previous reports have confirmed our observations including a recent publication by Sudha et al (2020) [ 52 ] to demonstrate tumor reduction by resveratrol and publications by Wang et al (2019) [ 53 ] and Zhang et al (2019) [ 54 ] that demonstrated the beneficial effect of resveratrol on DSS-induced colitis but at 80,100 mg/kg resveratrol use. In addition, cell-based modulation of follicular tumorigenesis (at 300 µM) [ 55 ] highlights the importance of our findings at 50–100 µM for our resveratrol derivatives. Because of the effectiveness of several aspirin-resveratrol derivatives towards both growth and NFκB inhibition (such as C3 and C11), these aspirin-resveratrol derivatives could be potent inhibitors of inflammation-driven malignant transformation.…”
Section: Discussionmentioning
confidence: 96%